2010
DOI: 10.1111/j.1423-0410.2009.01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ABO blood group allele and identification of three novel alleles in the Chinese Han population

Abstract: The detailed frequencies distribution of ABO alleles was studied in the Chinese Han population. We identified 14 alleles, including 3 novel alleles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 22 publications
3
72
0
1
Order By: Relevance
“…For example, the A101 , O01 , B101 , A102 , and O02 alleles are common in Asian populations [14]. Alleles such as O04 and A205 are found in the Han Chinese, and allele O06 is found in the Japanese [56]. Rare alleles such as cis-AB01 , cis-AB02 , and cis-AB06 are more frequently encountered in the Japanese, Korean, and Chinese populations [578].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the A101 , O01 , B101 , A102 , and O02 alleles are common in Asian populations [14]. Alleles such as O04 and A205 are found in the Han Chinese, and allele O06 is found in the Japanese [56]. Rare alleles such as cis-AB01 , cis-AB02 , and cis-AB06 are more frequently encountered in the Japanese, Korean, and Chinese populations [578].…”
Section: Introductionmentioning
confidence: 99%
“…Further sequencing analysis of exons 6 and 7 of the ABO gene revealed the mutation sites of the four CisAB members. It has been well known that sequence variations were detected in the six different CisAB alleles compared with some of the ABO alleles [9][10][11][12][13][14][15] (Table 2) (Table 2), which are identical to the well-documented CisAB01 /B101 genotype [9].…”
Section: Resultsmentioning
confidence: 99%
“…They found that the unique mutations of 467 C > T, 796 C > A and 803 G > C explained the molecular genetic basis of the CisAB phenotype. Six types of CisAB genotypes have been reported since it was first described in 1964: CisAB01 (467 C > T and 803 G > C) [11], CisAB02 (526 C > G, 657 C > T, 703 G > A and 803 G > C) [12], CisAB03 (297 A > G, 526 C > G, 657 C > T, 700 C > T, 703 G > A, 796 C > A, 803 G > C and 930 G > A) [13], CisAB04 (467 C > T and 796 C > A) [13], CisAB05 (163 T > C, 179 C > T, 467 C > T and 803 G > C) [14] and CisAB06 (297 A > G, 657 C > T, 703 G > A, 796 C > A, 803 G > C and 930 G > A) [15]. The incidence of the CisAB phenotype is very low; it is approximately 0.0014% in the Japanese population.…”
Section: Article In Pressmentioning
confidence: 99%
“…Common alleles of ABO blood groups are A101, A102, B101, O01, and O02 (Zhu et al, 2010). To date, approximately 200 ABO alleles have been identified (Blumenfeld and Patnaik, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although their frequencies are relatively low, these alternate alleles serologically manifest mainly as differentially expressed ABO blood group antigens and by phenomena such as the weakening of antigen strength, mixed-field-agglutination, and inconsistent positive and negative stereotypes in blood typing (Issitt and Anstee, 1998). Furthermore, molecular diagnostic techniques have also been used to clarify the molecular mechanisms of these partial ABO subtypes (Seltsam et al, 2003;Roubinet et al, 2004;Sun et al, 2006;Zhu et al, 2010). We found one case of the A 2 B subtype in clinical blood typing, and here report its molecular mechanism and results of the pedigree analysis.…”
Section: Introductionmentioning
confidence: 95%